2023
DOI: 10.1155/2023/8617388
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization and Optimal Operation of a 140 kVA Inverter in On-Grid Mode Using Mamdani Controllers in Cascade

Abstract: This paper addresses the synchronization and operation of a 140 kVA inverter system connected to the main grid as part of a decentralized microgeneration system. The considerations for the supply of electrical energy stored in battery banks, mostly of photovoltaic origin, involve a study of the details of a rigid nonlinear system, which parallels the generation and distribution standards typical of hydroelectric and thermoelectric plants. Considering aspects related to power electronics operation, this paper p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…In contrast, the average current in the inductor measures 265. 15 [𝐴], considering the loop, for a nominal load. It can be observed that during the transient, the voltage does not exhibit significant overshoot, and its increase is relatively gradual.…”
Section: Closed-loop Behavior Under Nominal Loadmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, the average current in the inductor measures 265. 15 [𝐴], considering the loop, for a nominal load. It can be observed that during the transient, the voltage does not exhibit significant overshoot, and its increase is relatively gradual.…”
Section: Closed-loop Behavior Under Nominal Loadmentioning
confidence: 99%
“…Furthermore, Srikanth et al [7] presented a bidirectional operation of a dual-mode PV inverter for seamless power transfer between DC and AC loads along with the grid interface. The research of Rodríguez-Flores et al [15] is cited for expanding the use of fuzzy logic in electrical applications, who demonstrated the application of a proportional-integral controller and a proportional controller based on Mandani fuzzy logic and connected in cascade to determine the reference generation power and the reference phase shift of the generator in order to perform synchronization between the main grid and a decentralized microgeneration system through a 140 [kVA] inverter.…”
Section: Introductionmentioning
confidence: 99%